The Practice of Selling and Buying Sea Cucumbers in an Islamic Business Perspective on Barrang Lompo Island, Sangkarrang Islands District, Makassar City - Muhammad Najib kasim; Sri Wahyuni; Ratih Ratih (Jurnal Ar-Ribh, 2022)
This study aims to determine the practice of buying and selling sea cucumbers in an Islamic business perspective on Barrang Lompo Island, Sangkarrang Islands District, Makassar City. The type of research used is the Qualitative Research Method. The processed data is the result of interviews with sellers and buyers and fishermen looking for sea cucumbers. The data collection method used in this research is Interview, Observation and Documentation. The results showed that the sale and purchase of sea cucumbers was carried out with murabahah transactions. Murabahah buying and selling is a purchase by one party to then be sold to another party who has submitted an application for the purchase of an item with a transparent profit or additional price. Sellers and buyers of sea cucumbers on Barrang Lompo Island have implemented an attitude of honesty (siddiq) in doing business, sellers and buyers of sea cucumbers on Barrang Lompo Island have implemented a friendly and communicative attitude (Tablig) in doing business, sellers and buyers of sea cucumbers on Barrang Lompo Island have implemented a respectful attitude. trusted (trust) in business. In the practice of buying and selling sea cucumbers on Barrang Lompo Island, there are supporting and inhibiting factors. The supporting factors include: The majority of the people of Barrang Lompo Island are Muslim, The knowledge capacity of the Barrang Lompo Island community about Islam has increased, Traders and buyers have realized sharia principles such as showing an attitude of honesty, justice, friendly and communicative (tabligh), and ar-ridha. The solidarity attitude of the people of Barrang Lompo Island is still close, the attitude of helping (ta'awun) has become the culture of the people of Barrang Lompo Island. While the inhibiting factors are as follows: Because the method of catching sea cucumbers is carried out by taking them directly on the seabed with a deep enough depth, it can cause divers to experience paralysis, if the weather is not good then the fishermen will be hampered from going down to the sea looking for sea cucumbers, some people are still traditional.